Homing choice and platform pricing strategy - Shiva Shekhar (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2017)
We compare a discriminatory pricing regime with a non-discriminatory regime in a competitive bottleneck model where content providers endogenously sort into single or multi-homers. We find that consumer prices rise when the share of single-homers increases in the non-discriminatory case, while they stay constant in the discriminatory pricing regime. A discriminatory pricing regime leads to higher platform profits than the non-discriminatory regime when the share of single-homers are relatively high. When the share of single-homers is relatively high (low), the discriminatory pricing regime leads to higher (lower) consumer surplus and social welfare when compared with the non-discriminatory regime.
Keywords: D43; L14; L82; L13; 330; price discrimination; two-sided markets; platforms; platform competition; network effects